Beothuk bark canoes : An analysis and comparative study - Marshall, Ingeborg, 1929- (Book collections on Project MUSE., 1985)
A detailed analysis of Beothuk canoes shows that there are two functionally different canoe designs, one specialized for ocean navigation while the second was more versatile. An analysis of hull forms indicates regional preferences and developments.